2013
DOI: 10.1016/j.ihj.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial abscess secondary to staphylococcal septicemia: Diagnosis with 3D echocardiography

Abstract: A 56 years old gentleman with staphylococcal septicemia with metastatic abscesses in spleen and heart. Real time 3D trans thoracic echocardiography could not only confirm the diagnosis of myocardial abscess but also well delineate it and identify adjacent structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…S . aureus is also the most common cause of bacterial myocarditis, with fatal outcomes [ 108 110 ]. Currently, there are no murine models to study MRSA induced myocarditis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S . aureus is also the most common cause of bacterial myocarditis, with fatal outcomes [ 108 110 ]. Currently, there are no murine models to study MRSA induced myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Current models of IE require anesthetizing C57BL6/J mice and physically damaging their heart valve using a catheter [106,107]. S. aureus is also the most common cause of bacterial myocarditis, with fatal outcomes [108][109][110]. Currently, there are no murine models to study MRSA induced myocarditis.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…However, they presented five characteristic echocardiographic findings, including prosthetic valve rocking, sinus of Valsalva aneurysm, anterior aortic root thickness of 10 mm or greater, posterior aortic root thickness of 10 mm or greater, perivalvular density in a septum of 14 mm or greater, and reported that the presence of one or more of these findings was associated with a positive predictive value of 86% and a negative predictive value of 87% for the presence of perivalvular abscess. Real-time 3D TTE in a patient without valvular inflammation has also been reported to describe detailed structure of a septal myocardial abscess with irregular septation (Jariwala et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…C57BL6 mice are typically used as background strains for the IE model [81]. S. aureus is also the most common cause of rare bacterial myocarditis, with fatal outcomes in some cases [82][83][84]. Currently, there are no murine models to study MRSA induced myocarditis.…”
Section: Discussionmentioning
confidence: 99%